EFEKTIVITAS PENAGIHAN PAJAK DALAM MENINGKATKAN PENERIMAAN PIUTANG PAJAK - Febriana, Diah; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to find out the effectiveness of tax collection with a letter of reprimand and forced letter inorder to improve the revenue of tax receivable at KPP Pratama Surabaya Rungkut. This research has beencarried out by using qualitative descriptive with the data source is the primary data and the secondary data. Thedata collection technique has been done by using interview and documentation. The data analysis technique hasbeen carried out by using descriptive analysis. The result of this research shows that the effectiveness of taxcollection with a letter of reprimand and forced letter in order to improve the revenue of tax receivable in 2014and 2015 relatively ineffective. These can be seen from the success percentage of collection is less than 60percent. It is caused by the contribution level to the tax revenue is categorized small with the achievement isbelow 10 percent. Therefore, it is recommended for the KPP Pratama Surabaya Rungkut is required to improvethe performance of the department of collection and gives socialization to the taxpayer related to the importanceof paying tax.Keywords: Effectiveness, a letter of reprimand, forced letter, revenue of tax receivables.